Das imagens às palavras: a relevância do contexto para o processo de construção de sentidos, através da inter-relação das linguagens verbal e visual, no conto “O Pequeno Príncipe”, de Antoine de Saint-Exupéry - Santos, Claudeney Rocha (2023)
Training proficient readers has been the great challenge for teachers in the face of the rapid advancement of technology and information, which constantly provides students with contact with texts constructed using varied semiotic resources in the most diverse social practices. Given this context, centered on an interactive and reflective conception of reading, this work aims to suggest a proposal for intervention to improve reading comprehension of literary texts based on the relevance of the context for the interrelationship of verbal and visual languages in the process of meaning construction in the short story The Little Prince, by Antoine de SaintExupéry, from the perspective of literary literacy. To this end, among the theoreticalmethodological approaches, bibliographic research based on Lakatos was adopted for this study; Marconi (2001) and qualitative action research based on Thiollent (1985), having as empirical field the Nações Unidas State School, in Aquidabã-SE city. For data collection, we chose a questionnaire to survey the reader profile on Google Forms and a written questionnaire on the analysis of the interrelationship of image and verbal codes in the short story “O kiss of little word”, by Mia Couto, since we propose a didactic sequence based on the theoretical assumptions of Dolz, Noverraz and Schneuwly (2004) and Cosson (2021) with the short story The Little Prince, by Antoine de Saint-Exupéry (1943). As a theoretical apparatus, we also seek subsidies related to conceptions and strategies of reading and reading comprehension (PCNs, 1997; LDBEN 1996; BNCC 2017; BNCC 2018; KOCH & ELIAS, 2021; LEFFA, 1996; MARCUSCHI, 2008; KLEIMAN, 2004; SOLÉ, 1998), concepts of literacy (SOARES, 2006; KLEIMAN, 1995; STREET, 1994), the law and adequate schooling of literature (ISER, 1999; COMPANHON, 2003; SOARES, 2006), literary literacy (COSSON, 2021) , multiliteracy (GRUPO DE NOVA LONDRES, 1996; ROJO, 2012; ROJO, 2013), multimodality (KRESS AND van LEEUWEN, 2006) with the purpose of realizing the potential of visual language in the construction of meaning in the process of reading comprehension.